The Outdoor Study Activity by Utilizing Wonosoco Tourism Village as A Learning Resource of Social Studies - Fatmawati, Noor; Setyowati, Dewi Liesnoor; Utomo, Cahyo Budi (Universitas Negeri Semarang, 2018)
The majority of learning activity process is indoor activity in the classroom, it tends for the ability of students that are memorizing, remembering, and collecting information. The aim of this research is to analyze outdoor study activity using Wonosoco Tourism Village as the learning resource and the obstacles. Qualitative research method is using by ethnography, phenomology, and study case approaches. The purpose of this research is to analyze the potential of Wonosoco Tourism Village as learning resource of social studies. The main informants are social studies teacher and 6 students in the State Junior High School 3 Satu Atap Undaan District Kudus Regency. Analyzing data is using Spradley Model by domain analysis step, taxonomy, componential, and cultural theme. The results show that in the preparation step, teacher prepares lesson plan, worksheet, outdoor study place, and time management. Than students prepare stationary, listen to the material, and receive worksheet. The implementation step, teacher explains the material, divides group and gives worksheet, also evaluates and keeps on eye for students, meanwhile students do observation, interview, and discussion. In evaluation step, teacher comes to each group to give the feedback and ask them to do presentation. The obstacle are during the use of teak tree forest, students can not go to forest area deeply so they can not get optimal result in exploring biotic environment, using of settlement and society life, teacher feels difficult in giving attention and evaluating students activity so because they are uncontrollable, also feel difficult in time management and preparation of the object for the learning resource which is relevant with the material, students are also feel difficult to be focus.